Predictors of Alcohol Consumption Among Younger Adults During the First Phase of the COVID-19 Pandemic - Brandt, Lasse; Evens, Ricarda; Reiche, Simon; Marek, Roman M.; Moon, Daa Un; Groß, Elisa; Romanello, Amy; Masah, Dario Jalilzadeh; Scicchitano, Matteo; Gutwinski, Stefan; Montag, Christiane; Majić, Tomislav; et al. (Frontiers in Psychiatry, 2021)
Background: The COVID-19 pandemic may lead to negative mental health effects but the effect on alcohol consumption among younger adults is unclear. We assess predictors of change in alcohol consumption during the first phase of the COVID-19 pandemic among younger adults. Methods: This cross-sectional internet-based survey was part of an overarching project, the Corona Drug Survey, which was conducted from April 30 to August 25, 2020. Participants of any sex and ≥18 years old were included. The primary outcome measure was change in alcohol consumption during the early COVID-19 pandemic. We implemented an ordinal logistic regression to assess the effect (odds ratio [OR] and 95% confidence interval [CI]) of the following predictors: quarantine restrictions on leaving the residence, number of individuals in the household, problematic alcohol consumption before the pandemic (CAGE [cutting down, annoyance by criticism, guilty feeling, and eye-opener] score), personal concern regarding the pandemic, age, and sex. Results: 3,321 participants with a mean age of 32 (SD: 13) years were included in this study. 70.4% of participants reported less or unchanged alcohol consumption in the recent 4 weeks of the pandemic compared to before the pandemic. A higher number of individuals in the household was associated with a reduced alcohol consumption (OR=0.844; 95% CI=0.792-0.900). No quarantine restrictions on leaving the residence (OR=1.593; 95% CI=1.397-1.817), a higher age (1.006; 1.001-1.011), and female sex (compared to males: 1.206; 1.062-1.371) were associated with an increase in alcohol consumption. The CAGE score before the pandemic (OR=0.983; 95% CI=0.931-1.037) and the pandemic concern (0.927; 0.857-1.003) were not associated with a significant change in alcohol consumption. Celebrations were no longer frequent drinking occasions during the pandemic compared to before the pandemic. The majority of participants (60.9%) did not use alcohol drinking as a coping mechanism to mitigate negative effects of the pandemic. Interpretation: In this cohort of younger adults with fewer celebratory drinking occasions, restrictions on leaving the residence and the number of persons in the household were the strongest predictors of reduced alcohol consumption during the early phase of the pandemic.